PRVI SLOVANSKI PRIJEVOD MOLIEROVOG GEORGESA DANDINA I NJEGOVE SOCIOLINGVISTIČKE I DRAMATURŠKE IMPLIKACIJE (Филолошке студије, 2019)
Franjo Krsto Frankopan partly translated Molière's Georges Dandin into Slovenian in 1671, a fact which has not been sufficiently explored and even recognised so far. This article suggests that Frankopan's translation should be interpreted within the context of his efforts against the Habsbourgs where his choice of the Slovenian language undoubtedly had certain socio-linguistic and political implications which would deserve further research.